Early formation of belite in cement clinker raw materials with slag. Issue 6 (20th June 2021) - Viggh, Erik; Eriksson, Matias; Wilhelmsson, Bodil; Backman, Rainer
Abstract : Analytical methods for characterising cement raw meal during heating in different atmospheres were investigated. The effect of replacing limestone with 10 wt% slag on the formation of incipient belite and precursors of the clinker liquid in the temperature range 600–1050°C was quantified using thermogravimetry, X-ray diffraction and equilibrium calculations. The results showed that when calculating the lime saturation factor, slags were favoured to sand, resulting in lower amounts of quartz and C2 S in the samples containing slag than the reference sample. This suggests that silicon dioxide in slag minerals did not react in this temperature range. The multi-component equilibrium results supported the phase formation sequence established. Allowing for the possible kinetic influences the potential solids solutions offered with the software was a valuable asset. The results showed that the effect of using slags to reduce the carbonate and sand content in a raw meal on potential amounts of incipient C2 S was negative. At present, more detailed knowledge is needed regarding how blast-furnace slag and basic oxygen furnace slag contribute to the formation of intermediary compounds such as incipient C2 S, C3 A, C2 F and C4 AF in the solid phase at temperatures over 1050°C and affect the formation of C3 S.